Optimization design and experiment on feeding and chopping device of silage maize harvester - Chen, Meizhou; Xu, Guangfei; Wei, Maojian; Li, Xiaowei; Wei, Yuanzhen; Diao, Peisong; Cui, Peide; Teng, Shaomin (International Journal of Agricultural and Biological Engineering, 2023)
Horizontal feeding devices and plate hob chopping devices are the key component of silage maize harvester. To solve the problem of feeding blockage, reduce energy consumption, and improve the chopping quality of the chopping device a horizontal different diameter five-rollers device (HDDFD) was designed and the plate hob chopping device was simultaneously optimized and analyzed. Through the dynamic analysis, the feeding conveying speed was determined to be 2.0-4.5 m/s. The distance equation of the actual and theoretical cutting-edge curve and the position of the fixed blade were finally obtained. Single factor and response surface orthogonal tests in the bench site were carried out with feeding speed, rotating speed of chopping cylinder, feeding amount, and feeding direction as influencing factors, standard grass length rate (SGLR), and energy consumption per unit mass (ECPUM) as evaluation indexes. The optimal working parameters for chopping performance could be concluded as a feeding speed of 3.39 m/s, rotating speed of the chopping cylinder of 1016.17 r/min, feeding amount of 8.04 kg/s, and feeding direction of 52.2°. In addition, the SGLR and ECPUM were obtained as 95.35% and 37.63 kJ/kg, respectively. The relative error between the experimental results with round parameter combination and the predicted value was verified to be less than 5%. Field tests verified the reliability of the optimized feeding and chopping device. It can be seen that the HDDFD and optimized plate hob chopping device can meet the requirements of mechanized silage harvesting which obviously improves the working quality and reduce the energy consumption of chopping. Keywords: silage maize, feeding device, chopping device, stand grass length ratio, energy consumption DOI: 10.25165/j.ijabe.20231603.7922 Citation: Chen M Z, Xu G F, Wei M J, Li X W, Wei Y Z, Diao P S, et al. Optimization design and experiment on feeding and chopping device of silage maize harvester. Int J Agric & Biol Eng, 2023; 16(3): 64–77.